The Relationship between Quality of Service Providing Software Systems and User Satisfaction in Selected Hospitals of Tehran University of Medical Sciences - Zahra Maebood Mojdehi; Amir Ashkan Nasirirour; Pouran Raeissi (Tehran University of Medical Sciences, 2016)
Background: Medical centers and hospitals need to expand internet, Application Service Providing (ASP) to convert it to a long-lasting choice to compete. Hence, the present study carried out with the aim of determining the relationship between quality of service providing software systems and customer satisfaction in selected hospitals of Tehran University of Medical Sciences with similar hospital information systems. Materials and Methods: This study was a descriptive-analytical and correlation one. The study population consisted of revenue and clearance employeeschr('39') unit in selected hospitals. Study method was census using Kim et al questionnaire. Descriptive statistics such as frequency, percentage and average; and inferential statistics like Kolmogorov-Smirnove Test and Pearson correlation coefficient utilized in order to data analysis. Results: There was a significant positive correlation between quality of Application System Provider variables and users satisfaction in order of severity in system quality (r = 0.734, P = 0.01), service quality(r=0.721, P = 0.01) and information quality(r=0.521, P = 0.01). As, system quality had the most impact on userschr('39') satisfaction. Conclusion: There was a significant relationship between the quality of Application Service Providing (ASP) with the userschr('39') satisfaction in selected hospitals of Tehran University of medical sciences. Although, all variables had positive and significant relationship with user satisfaction, their average was less than moderate limit. So, the health managers are advised to consider these issues in management methods.